Musikaliska synpunkter på en revision av Den svenska psalmboken 1986 - Dillmar, Anders (Svenskt gudstjänstliv, 2020)
The last ambitious revision of the Swedish hymnal was instigated in a hymnal committee in 1969 and resulted in the Swedish hymnal of 1986 (Den svenska psalmboken). Since that point the Church of Sweden has produced additions and appendices of a semi-official hymnal status: Psalmer i 90-talet (“Hymns in the 1990s”) and Psalmer i 2000-talet (“Hymns in the 2000s”), in addition to further collections of less official status. This study revisits the 1986 revision and later work, trying to identify aspects of successful choices and methods with those less successful. It is argued that it is vital to let musical aspects be at the core of the matter in committee work, and that work with hymnals has to follow principles and methodologies that are well-reflected and transparent.